2022
DOI: 10.1136/bmjopen-2021-049191
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hindrance stressors on the emotional exhaustion among front-line healthcare workers in the recuperation period during the COVID-19 epidemic in China: a prospective cross-sectional study

Abstract: ObjectivesThis study aimed to examine the influence and conditioning process of hindrance stressors on the emotional exhaustion of the front-line healthcare workers during recuperation, examine the potential mediating process of rumination, and explore the moderating role of organisational and family factors.SettingThis cross-sectional study was conducted during 12–20 July 2020. Total 418 questionnaires were collected from front-line healthcare workers by random cluster sampling. Hierarchical regression was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This study's findings align with previous research. Similarly, recent studies focusing on employees in the hospitality industry during the COVID-19 pandemic and on frontline healthcare workers found that servant leadership mitigated employees' emotional exhaustion and potential negative impacts [23,24]. Despite locating studies examining this effect in service and health sectors, no research was reached relating to high-pressure, high-risk occupations like firefighters or disaster relief workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study's findings align with previous research. Similarly, recent studies focusing on employees in the hospitality industry during the COVID-19 pandemic and on frontline healthcare workers found that servant leadership mitigated employees' emotional exhaustion and potential negative impacts [23,24]. Despite locating studies examining this effect in service and health sectors, no research was reached relating to high-pressure, high-risk occupations like firefighters or disaster relief workers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the decrease in emotional exhaustion due to servant leadership played a significant role in this interaction. Another study revealed that among 418 frontline healthcare workers, servant leadership reduced hindrance stressors during the pandemic crisis, thereby lessening the experience of emotional exhaustion [24]. While no studies directly addressing DRWs were reached in the literature review, servant leadership significantly reduces emotional exhaustion, preventing employees from having negative experiences in crises.…”
Section: Servant Leadership and Emotional Exhaustionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agar memperkaya hasil reviu, penelitian selanjutnya dapat memperluas lingkup desain studi dari jurnal artikel dengan mencakup artikel dengan metode penelitian kualitatif, eksperimen, dan mixedmethod. Selain itu, gaya kepemimpinan tidak secara eksklusif berperan sebagai variabel independen saja, tapi juga dapat berperan sebagai variabel moderasi (Johnson et al, 2022); (Wang et al, 2022) maupun mediasi (Ahmad et al, 2021); (Caputo et al, 2023). Penambahan peran gaya kepemimpinan sebagai variabel moderasi dan mediasi juga akan memberikan pemahaman yang lebih luas mengenai alur kerja setiap variabel yang berkaitan dengan gaya kepemimpinan.…”
Section: Hasil Penelitian Pengaruh Gaya Kepemimpinan Dalam Penelitian...unclassified